Optioneering analysis for connecting Dogger Bank offshore wind farms to the GB electricity network. (June 2016) - Nieradzinska, K.; MacIver, C.; Gill, S.; Agnew, G.A.; Anaya-Lara, O.; Bell, K.R.W.
Abstract: This paper outlines possibilities for connecting 2.4 GW of power from two separate wind farms at Dogger Bank in the North Sea to the GB transmission system in Great Britain. Three options based on HVDC with Voltage Source Converters (VSC HVDC) are investigated: two separate point-to-point connections, a four-terminal multi-terminal network and a four-terminal network with the addition of an AC auxiliary cable between the two wind farms. Each option is investigated in terms of investment cost, controllability and reliability against expected fault scenarios. The paper concludes that a VSC-HVDC point-to-point connection is the cheapest option in terms of capital cost and has the additional advantage that it uses technology that is commercially available. However, while multi-terminal connections are more expensive to build it is found that they can offer significant advantages over point to point systems in terms of security of supply and so could offer better value for money overall. A multi-terminal option with an auxiliary AC connection between wind farms is found to be lower cost than a full multi-terminal DC grid option although the latter network would offer ability to operate at greater connection distances between substations. Highlights: Comparison different electrical connection topologies for offshore wind farms. Carries out a cost comparison between HVDC connection topologies. Analysis of the costs associated with reliability of electrical connection equipment. The AC auxiliary option is best due to lower protection costs and higher revenue but its use is limited by distance.